Identifikasi Potensi Ekowisata Hutan Kota Pulau Bungin Kabupaten Kuantan Singingi - Budi Helianto; Defri Yoza; Yossi Oktorini Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
At this time the building of forest city pulau bungin still in step as the trees habitats in the middle of city that’s why need the data about potency ecotourism of forest city pulau bungin located at kota taluk kuantan, kuantan singingi regency. This research doing at forest city pulau bungin, kuantan singingi regency, riau province, helded at April-mei 2016. From the result of this reseach can conclude that the potency ecotourism of forest city located in forest city pulau bungin is pendopo, traditional track, jogging track, bridge, fruits forest, chair. The potency ecotourism of that very interesting in forest city pulau bungin is Fruits tree with precentage 48% and interesting category. Key words: Forest city Pulau Bungin, Potency Ecotourism